Nonlinear modeling of target leverage with latent determinant variables: New evidence on the trade-off theory - Ralf Sabiwalsky (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
The trade-off theory on capital structure is tested by modelling the capital structure target as the solution to a maximization problem. This solution maps asset volatility and loss given default to optimal leverage. By applying nonlinear structural equation modelling, these unobservable variables are estimated based on observable indicator variables, and simultaneously, the speed of adjustment towards this leverage target is estimated. Linear specifications of the leverage target suffer from overlap between the predictions of various theories on capital structure about the sign and significance of determinants. In contrast, the framework applied here allows for a direct test: results confirm the trade-off theory for small and medium-sized firms, but not for large firms.
Keywords: G32; G33; C61; 330; Capital structure; nonlinear; latent variables; trade-off theory; Kapitalstruktur; Betriebswirtschaftliches Ziel; Nichtlineare Optimierung; Multivariate Analyse; Theorie; USA; Welt